EP.TU.4973 year oncological outcomes of robotic-assisted versus laparoscopic rectal cancer resections – a single centre experience. (28th October 2021) - O'Connell, Lauren; Ramjit, Sinead; Nugent, Tim; Neary, Paul; Hafeez, Adnan; O'Riordain, Diarmuid
Abstract: Background: Robotic-assisted minimally invasive surgery (MIS) for rectal cancer is a relatively new technique. Studies to date suggest that short term outcomes including TME quality, margin status, lymph node retrieval and 30-day morbidity and mortality are equivalent in robotic-assisted and laparoscopic MIS for rectal cancer. By contrast, there is a paucity of data on the medium and long-term oncologic safety of robotic-assisted comparative to laparoscopic surgery for rectal cancer. Methods: A retrospective review was conducted of all robotic-assisted (n = 31) and laparoscopic (n = 23) rectal cancer cases performed at our institution between January 2016 to December 2018. Inclusion criteria were patients scheduled electively for a laparoscopic or robotic-assisted resection of rectal cancer (anterior resection or abdomino-perineal resection). Patients with distant metastases at presentation, those who proceeded to surgery as an emergency and those with a non-colorectal primary were excluded from analysis. Results: A total of 54 (n = 54) cases met the inclusion criteria and were included in the final analysis. The median follow-up was 34 months. Of the 54, 21 patients received neoadjuvant chemoradiotherapy prior to definitive surgery. No significant difference was detected in local recurrence rates (p = 0.5), overall survival (p = 0.7) or disease-free survival (p = 0.8) between the robotic-assisted and laparoscopic cohorts. Conclusion: In this series, robotic-assisted rectal cancer resections were associated with equivalent medium term oncological outcomes as laparoscopic procedures. However, given the small numbers in this cohort, outcomes from larger scale datasets will be required to confirm these results.